The specifics and functions of the concepts of LIFE and DEATH in V. Y. Bryusov's poetry - Glazkova, Marina Mikhailovna; Ilyina, Svetlana Anatolevna (Филология: научные исследования, 2024)
The object of the study are poems representing such thematic layers as love lyrics; urban lyrics, including poems dedicated to Venice; the theme of death; the theme of Vikings; great figures of the past; apocalyptic themes. The paper actualizes the importance of studying Bryusov's poetry in the aspect of cognitive linguistics, examines the essence of the concepts. The place of the concepts of LIFE and DEATH in the hierarchical structure of the conceptual sphere is analyzed, their meanings are revealed based on the lexicographic material of dictionaries, representing, along with the primary meanings, various associative lexical units, including mythologems that arose on the basis of cognitive metaphorization, which, being representatives of concepts, fill slots, form a frame structure, while the frame qualifies as the core of the concept. The analysis of poems allowing to recreate the linguistic and artistic worldview of the poet, the keys to understanding which are the basic concepts of LIFE and DEATH, and to determine their specificity and role, is carried out. The following methods were used in the research process: the method of discursive analysis, which allowed us to study the interacting denotative and conceptual structures that organize the semantic space of each lyrical work under consideration in the context of Bryusov's poetry; the cultural and historical method, which contributed to the identification of connotative meanings representing the concepts of LIFE and DEATH; the hermeneutic method, which made it possible to analyze the poetics of poems. As a result of the study, the authors came to the following conclusions. Organizing a system of poetic creativity, vividly embodying the main motive, the motive of duality, the concepts of LIFE and DEATH undergo semantic contamination based on the intersection of their frame networks and form a single bipolar concept of LIFE/DEATH. An integral phenomenon, Bryusov's concept of LIFE/DEATH is multifunctional: as a figurative means, this structural unit creates the poet's idiosyncrasy; plays a text-forming role; organizes the main motives that allow Bryusov to carry out a discourse relevant to him and his contemporaries about the problem of the meaning of life and its eternity. The scientific novelty lies in the fact that the work of V. Y. Bryusov, from the point of view of the conceptual sphere and conceptualization, has not been sufficiently studied. For the first time, the comprehension of V.Y. Bryusov's linguistic picture of the world was realized through the concepts of LIFE and DEATH, which are fundamental in his work.